Integrative function of proprioceptive system in the acute effects of whole body vibration on the movement performance in young adults - Maslova, Olga; Shusharina, Natalia; Videnin, Arseniy; Pyatin, Vasiliy (Frontiers in Sports and Active Living, 2024)
Background The proprioceptive system coordinates locomotion, but its role in short-term integration and recovery of motor activity in imbalance of motor patterns and body remains debated. The aim of this study is investigating the functional role of proprioceptive system in motor patterns and body balance in healthy young adults. Methods 70 participants (aged 20.1 ± 0.3) were divided into experimental groups EG1 (n = 30), EG2 (n = 30), control group (CG, n = 10). EG1 performed single WBV session on Power Plate (7 exercises adapted to Functional Movement Screen (FMS). EG2 performed single session of FMS Exercises (FMSE). CG didn't perform any physical activity. All participants performed pre- and post-session of FMS and stabilometric measurements. Results FMS total score in EG1 increased by 2.0 ± 0.2 (p0 < 0.001), this was significantly differed (p0 < 0.001) from EG2 and CG. Acute effects of WBV and FMSE on rate of change and standard deviation (SD) of pressure center (COP) were shown in all groups during Static Test (p0 < 0.01). SD increased (p0 < 0.01) in Given Setting Test in EG1 and EG2, and in Romberg Test (p0 < 0.001) in EG1. Length, width and area (p0 < 0.01) of confidence ellipse, containing 95% of the statokinesiogram points, decreased in Static Test in EG1; width and area (p0 < 0.01) decreased in EG2 group. Significant (p0 < 0.01) decrease in Given Setting Test was in EG1, and significant (p0 < 0.01) increase was in Romberg Test (open eyes) in CG. Maximum amplitude of COP oscillations: significantly (p0 < 0.01) decreasing along X and Y axes in EG1 and EG2, and along Y axis in CG during Static Test; along Y axis (p0 < 0.01) in all groups during Given Setting Test. Significant differences were identified (p0 < 0.01) in calculated energy consumption for COP moving during all stabilometric tests. However, inter-group differences in COP after acute WBV and FMSE sessions have not been identified. Conclusions Acute WBV session eliminates the deficits in motor patterns which is not the case after acute FMSE session, which, according to our integrative movement tuning hypothesis, is due to high activation of integrative function of proprioceptive system. Efficacy of WBV and FMSE on COP performance indicates a high sensitivity of postural control to different levels of proprioceptive system activity.